The right to withdraw the notification to leave the European Union under article 50 TEU: can we still save the marriage? - Alvim, Mariana (2019)
Article 50 TEU has caused considerable interest following its introduction in EU law, but mostly since the UK voted in favour of leaving the Union, a vote that provoked its first ever activation. However, this Article raises a few unanswered questions, such as if a Member State that formally notifies to the European Council of its intention to leave the EU, can it subsequently change its mind about this decision during the two-year period established in the Treaty. In the first part of the article, I intend to put the notification to leave the European Union under Article 50 of the TEU in perspective, elucidating the steps that have to be taken, and to address the silent aspects of Article 50. In the second Part, I will assess if a Member State that triggers Article 50 TEU, can still withdraw the notification to leave, once Article 50 TEU is completely soundless in this respect, and in doing so answer the central question of this article: “Can we still save the marriage?”